Thermal decomposition and chemical vapor deposition: a comparative study of multi-layer growth of graphene on SiC(000-1). Issue 55 (18th May 2016) - Convertino, D.; Rossi, A.; Miseikis, V.; Piazza, V.; Coletti, C.
ABSTRACT: This work presents a comparison of the structural, chemical and electronic properties of multi-layer graphene grown on SiC(000-1) by using two different growth approaches: thermal decomposition and chemical vapor deposition (CVD). The topography of the samples was investigated by using atomic force microscopy (AFM), and scanning electron microscopy (SEM) was performed to examine the sample on a large scale. Raman spectroscopy was used to assess the crystallinity and electronic behavior of the multi-layer graphene and to estimate its thickness in a non-invasive way. While the crystallinity of the samples obtained with the two different approaches is comparable, our results indicate that the CVD method allows for a better thickness control of the grown graphene.